2018
DOI: 10.1111/jbi.13422
|View full text |Cite
|
Sign up to set email alerts
|

Islands in the trees: A biogeographic exploration of epiphyte‐dwelling spiders

Abstract: Aim Epiphytic plants are isolated from each other by nonhabitat canopy elements and are thus expected to act as islands, the biodiversity of their inhabitants (e.g., spiders) conforming to island biogeographic predictions of species‐richness patterns. Although it has been shown that arthropod diversity decreases with decreasing epiphyte size, the effects of isolation have not yet been addressed. We studied the joint effect of isolation, spatial position, and size of epiphytic plants (canopy islands) on species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 52 publications
0
23
1
1
Order By: Relevance
“…Host organisms can be understood as living islands upon which entire communities, or even meta communities, of colonizers can live or feed, surrounded by an unsuitable matrix of non-host organisms (Gripenberg & Roslin, 2005;Gossner, Chao, Bailey, & Prinzing, 2009;Méndez-Castro, Bader, Mendieta-Leiva, & Rao, 2018;Patiño, Gómez-Rodríguez, Pupo-Correia, Sequeira, & Vanderpoorten, 2018;Vialatte et al, 2010). Many of the patterns and processes that occur on true islands can be transposed, with certain limitations, to hosts (Santos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Host organisms can be understood as living islands upon which entire communities, or even meta communities, of colonizers can live or feed, surrounded by an unsuitable matrix of non-host organisms (Gripenberg & Roslin, 2005;Gossner, Chao, Bailey, & Prinzing, 2009;Méndez-Castro, Bader, Mendieta-Leiva, & Rao, 2018;Patiño, Gómez-Rodríguez, Pupo-Correia, Sequeira, & Vanderpoorten, 2018;Vialatte et al, 2010). Many of the patterns and processes that occur on true islands can be transposed, with certain limitations, to hosts (Santos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The data used for this analysis are a subset of that used in Méndez-Castro et al (2018). We omitted 80 canopy islands located on secondary branches, for which we could not calculate the walking distance.…”
Section: Discussionmentioning
confidence: 99%
“…These canopy islands constitute microhabitats for many arthropods and other organisms (Rodgers & Kitching, 2011;Stuntz, Ziegler, Simon, & Zotz, 2002;Yanoviak, Nadkarni, & Solano J, 2006) and are arranged in 'archipelagos' in a three-dimensional non-habitat space (Bader, van Dunne, & Stuiver, 2000). In our previous work (Méndez-Castro et al, 2018) we showed how the isolation of such canopy islands had a significant, though small, effect on the spider diversity. Other studies on canopy islands have been unable to show such an effect (Richardson, 1999;Rodgers & Kitching, 2011;Wardle, 2003).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations